2014
DOI: 10.1007/s11064-014-1274-6
|View full text |Cite
|
Sign up to set email alerts
|

Neuroadaptations in the Striatal Proteome of the Rat Following Prolonged Excessive Sucrose Intake

Abstract: Obesity is a contemporary health problem of rapidly increasing prevalence. One possible cause of obesity is loss of control over consumption of highly palatable foodstuffs, perhaps mirroring the processes involved in drug addiction. Accordingly, the striatum may be a key neural substrate involved in both food and drug craving. We hypothesised here that prolonged exposure to 10% sucrose solution might cause neuroadaptations in the striatum that are analogous to those previously reported following prolonged expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…Proponents of the concept suggest that similarities between FA and other substance addictions, in particular, operant conditioning, effects of mood and stress, cue reactivity, craving, and impulsivity support food as an addictive substance (Ahmed et al, 2014; Berenson et al, 2015; Frayn et al, 2016; Kishinevsky et al, 2012; Pelchat et al, 2004). There is also some neural evidence supporting food as an addiction because of observations of downregulation of reward circuitry and difficulties with top-down cognitive control (Blum et al, 2014; Stice, Spoor, Bohon, et al, 2008; Volkow et al, 2003, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proponents of the concept suggest that similarities between FA and other substance addictions, in particular, operant conditioning, effects of mood and stress, cue reactivity, craving, and impulsivity support food as an addictive substance (Ahmed et al, 2014; Berenson et al, 2015; Frayn et al, 2016; Kishinevsky et al, 2012; Pelchat et al, 2004). There is also some neural evidence supporting food as an addiction because of observations of downregulation of reward circuitry and difficulties with top-down cognitive control (Blum et al, 2014; Stice, Spoor, Bohon, et al, 2008; Volkow et al, 2003, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Over time, the consumption of highly palatable foods may lead to neuroadaptations in brain reward centers involving the downregulation of D2 receptors, as seen in other substance addictions: motivation switches to a desire to ameliorate negative emotional or physiological states, such as depression, anxiety, irritability, or other somatic symptoms related to absence of the highly palatable food (de Macedo et al, 2016; Meule & Kubler, 2012; Parylak et al, 2011). To date, most of the evidence for this type of neuroplasticity in FA comes from animal studies (Ahmed et al, 2014; Johnson & Kenny, 2010; van de Giessen et al, 2013). …”
Section: Factors That Lead To the Formation Of Famentioning
confidence: 99%
“…Diet-induced obesity is associated with decreased tyrosine hydroxylase (TH) expression, the rate-limiting factor in the synthesis of dopamine in dopamine-relevant brain regions. [13][14][15] Furthermore, blunted striatal dopamine concentrations in diet-induced obesity have been described using several techniques, including total dopamine concentrations and/or dopamine turnover in the striatum in brain punches, 16,17 decreased extracellular concentrations measured with microdialysis, 18,19 and decreased evoked release with electrochemistry. 18 Only one study revealed an increase in nucleus accumbens dopamine measured with microdialysis in obesity prone rats on an 8-week high fat diet.…”
Section: Dopamine Metabolismmentioning
confidence: 99%
“…One such study observed decreased striatal DA concentrations following prolonged access to a sucrose solution in high-sucrose drinking rats [36], a finding also reported by this group in response to chronic exposure to ethanol [37]. Expression of tyrosine hydroxylase (TH), an enzyme involved in DA synthesis, was also decreased in the striatum of high sucrose-drinking rats.…”
Section: Effects Of Sugar On “Hedonic” Neural Systemsmentioning
confidence: 76%